Impacts of Export-platform FDI on the production of upstream industries - do third country size, trade agreements and local content requirement matter? Evidence from the Vietnamese supporting industries - Thanh Tam Nguyen-Huu; Minh Nguyen-Khac (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
This paper investigates the impacts of Export-platform foreign direct investment on the production of upstream industries through backward linkages. First, in a three-country model, these impacts are explained through a competition effect and a demand effect. Otherwise, such production is also affected by third country size, local content requirement, and power of trade agreements between the host and the third countries. Second, in the case of the Vietnamese supporting industries between 2000 and 2012, Export-platform FDI generates a negative effect. Moreover, local content requirement, and trade agreements between Vietnam and other countries positively impacts the production level of these industries whereas third countries size has an ambiguous impact.
Keywords: F23; F15; O1; 330; export-platform FDI; production of upstream industries; local content requirement; third country size; power of trade agreements; Vietnam